Towards long-term health - Berglund , Amelia (My University, 2023)
Living with a chronic illness, recovering from long term sickness or seeing someone close to you cope with health issues has a direct impact on how we view ourselves as individuals and our surrounding environment. It’s a situation that can make us feel vulnerable, in a lack of power will disturb our ability to be in full control of our life. Suffering from mental illnesses will sooner or later lead to a state where our bodies are trying to self-regulate - meaning that we will naturally shift the view on how we experience certain environments and which type of space we require to feel supported, safe and secure. This so-called supportive environment could, although, look different depending on the individual’s physical and psychological condition - meaning that the type of needed space will most likely shift from person to person and when our state of mind changes over time. Theories in the field of landscape architecture say that there are in general eight different characteristics that could be found in supportive environments. This master thesis will identify and translate those characteristics into indoor spaces. The result are meant to visualize how this theory can be used as a guideline for creating spatial experiences where inclusiveness, wellbeing and healing is possible. Having this guideline in mind when designing could lead to a better understanding about how our choices affect the user and a greater knowledge about what a supportive environment actually looks like. The aim of this master thesis is to design a place where people in need get help to cope with their emotional connection to long term sickness. The project will serve as an additional function to the already existing medical care system and explore through theories how health promotive elements in healthcare design could be used to create a healing, inclusive environment where people get the right tools for making life feel meaningful, fulfilled and manageable again.
Keywords: Supportive environments, Health-promotive design, psychology, mental health, holistic care, wellbeing